1994
DOI: 10.24266/0738-2898-12.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Marketing Preferences for Nursery Stock

Abstract: Consumer preferences as influenced by type of packaging, size of container, and price when purchasing landscape/nursery plants were determined. From February to May 1991, nearly 1,100 questionnaires were completed through personal on-site interviews conducted at flower/garden shows and traditional garden centers. Consumers preferred by almost a two to one margin to purchase trees as balled & burlapped stock and by almost a three to one margin, to purchase shrubs in containers. Over 90% of respondants norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One way Iowa companies can improve their competitive edge is to provide their clientele services or products not available at ''box stores.'' Research has shown that consumers will seek out and purchase from independent nursery and garden centers when they value trained and educated sales staff and high-quality products (Khatamian and Stevens, 1994;Makus et al, 1992;National Gardening Association, 2004;Safley and Wohlgenant, 1995). For example, in Illinois, 26% of homeowners reported receiving most of their information on ornamental plants from staff at retail nurseries and garden centers (Campbell, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…One way Iowa companies can improve their competitive edge is to provide their clientele services or products not available at ''box stores.'' Research has shown that consumers will seek out and purchase from independent nursery and garden centers when they value trained and educated sales staff and high-quality products (Khatamian and Stevens, 1994;Makus et al, 1992;National Gardening Association, 2004;Safley and Wohlgenant, 1995). For example, in Illinois, 26% of homeowners reported receiving most of their information on ornamental plants from staff at retail nurseries and garden centers (Campbell, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as telemarketing, written surveys, personal interviews, and focus-group studies have been used to collect consumer preference and market characteristic information. On-site personal interviews with garden center customers revealed a need for plant culture and descriptive information (Niemiera et al, 1993) and the importance of plant quality, availability of professional help, and plant selection for purchasing nursery stock (Khatamian and Stevens, 1994). A mail-in survey of 140 landscape firms was used to discover types of services provided by different types of firms (Florkowski et al, 1994).…”
Section: Additional Index Words Marketing Consumer Preference Product Evaluationmentioning
confidence: 99%
“…onsumers consider plant quality an overwhelmingly important factor when purchasing landscape plants (Brand and Leonard, 2001;Khatamian and Stevens, 1994). Quality considerations include dark green foliage (Baker, 1965), evidence of new growth, and absence of discolored or damaged leaves (Brand and Leonard, 2001).…”
mentioning
confidence: 99%